Estimation of rock strength from sonic log for Buzurgan oil field: A Comparison study - Hazem Hassan, Khalid; A. H. Abdul Hussien, Hassan (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
It is very difficult to obtain the value of a rock strength along the wellbore. The value of Rock strength utilizing to perform different analysis, for example, preventing failure of the wellbore, deciding a completion design and, control the production of sand. In this study, utilizing sonic log data from (Bu-50) and (BU-47) wells at Buzurgan oil field. Five formations have been studied (Mishrif, Sadia, Middle lower Kirkuk, Upper Kirkuk, and Jaddala) Firstly, calculated unconfined compressive strength (UCS) for each formation, using a sonic log method. Then, the derived confined compressive rock strengthens from (UCS) by entering the effect of bore and hydrostatic pressure for each formation. Evaluations the result of compared rock strength generated from two wells for the same formation and match the bottom and top of this formation in two wells. Based on the obtained results, a good agreement between values of unconfined compressive strength from well (50) and well (47) that used real along of drilling section. The net results of the match between rock strength for wells (BU-50, BU- 47) of five formations; Mishrif, Sadia, Middle lower Kirkuk, upper Kirkuk, and Jaddala were 97, 87, 96.5, 97, 86 %, respectively